Non‐invasive prenatal diagnosis for single gene disorders: experience of patients. (27th May 2013) - Lewis, C.; Hill, M.; Chitty, L.S.
<x xml:space="preserve">Abstract</x> The aim of this study is to explore women's experiences of using newly developed non‐invasive prenatal diagnosis (NIPD) for single gene disorders. Methods used in this study include qualitative one‐to‐one interviews with eight women with pregnancies at risk of achondroplasia, Apert syndrome, thanatophoric dysplasia or a neuromuscular condition. The results of the study show that the women were positive about an accurate, safe, and early test. Where the foetus was at increased risk of inheriting a genetic condition, the benefits of NIPD over invasive testing were that it reduced the period of uncertainty and worry by being conducted within the first trimester. For those women for whom there was a low recurrence risk, the period of uncertainty could be reduced and pregnancy 'normalized' earlier. For women who would not have risked invasive testing, NIPD enabled them to have an early diagnostic test that was more accurate than ultrasound. Where ultrasound abnormalities were detected, NIPD ended the 'diagnostic odyssey', enabling women to make practical and psychological preparations for the birth. NIPD conducted through specialist services was considered most appropriate. NIPD for these particular single gene disorders was appreciated by women and appears to be satisfactory. Further exploration of stakeholder views may be required to inform more widespread implementation of NIPD for a broader range of genetic conditions.